Pengukuran Efisiensi Komoditi Industri Kerajinan Kabupaten Agam Menggunakan Metode Data Envelopment Analysis (DEA) - Nurainun Pulungan; Arnellis Arnellis; Riry Sriningsih (UNIVERSITAS NEGERI PADANG, 2019)
Abstract – Small and medium industries of Agam regency consist of five groups where one of them is craft industry that has a number of business units in Agam regency. To get more profit, measurement of efficiency needs to be done to improve productivity of craft industry. Method to measure level of efficiency is Data Envelopment Analysis (DEA) method. DEA method is linear programming model based on the measurement of efficiency a Decision-Making Unit (DMU) and uses a lot of inputs and outputs. The units will be measured those efficiency are commodities of craft industries with the production capacity of quantity unit. The measurement of efficiency commodities generates efficient and inefficiency DMU by using model of DEA. The level efficiency of inefficient DMU can be improved by utilizing the value of slack variables. After target calculation for improvements inefficient DMU and measurements of efficiency is again so that value of efficiency increases.Keywords – Efficiency, Data Envelopment Analysis, Inefficiency, Slack, Target.